MEMBENTUK KARAKTER ANAK DALAM CERITA DONGENG NUSANTARA DI ERA DIGITAL - Arisandra, Martha Laila; Hafidh Nasrullah, Muhammad; Nurhayati, Anik; Ula, Mas (Universitas Djuanda, 2022)
This study literature examines how to build the character of children through learning materials of Indonesian’s fairy tale. This material can be taught on Indonesian subjects. The moral values in the Indonesia’s fairy tale is as follows: 1) individual moral values, such as: obedience, courage, sacrifice, etc. 2) social moral values, such as: working together, helping each others, affection, etc. 3) the value of religiosity, such as: believe in God and His power, tawakkal, patient, etc. Learning with fairy tale can be implemented with reading guide, assessment search, focused listing’s strategy.